Dynamic Mergers Effects on R&D Investments and Drug Development across Research Phases in the Pharmaceutical Industry - Ralph Siebert; Zhili Tian (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Pharmaceutical firms spend increasing amounts in mergers and acquisitions (M&As), which raises the question of whether sufficient investment is left after mergers to further develop firms' internal drug development capability. We evaluate the effects of M&As on firms' post-merger R&D investments and drug development capabilities across drug development phases. This study builds on a novel database that enables us to evaluate the post-merger effect at the research project level and across development phases. A further novel feature of the study is allowing measurement errors to enter firms' R&D investments. Our study adopts a structural equation modeling approach, which is appropriate for evaluating a system of equations through which we examine the direct and indirect merger effects on R&D capabilities across development phases. We find that M&As have a strong effect on firms' drug development at the late development phases through economies of scope. At the early development phases, M&As serve to replenish firms' drug pipelines. The study shows that M&As have a direct and negative effect on firms' R&D investments. However, the overall effect on R&D investments accounting for enhanced post-merger R&D capabilities and product approvals turns out to be positive. M&As can be an effective instrument for firms to acquire drug development knowledge and technology in late stages of the development process (Phases 3 clinical testing and regulatory filing). Our study provide empirical evidence that investments in M&As in late stage of drug development help firms' growth and increase firms revenue.
Keywords: L11; L13; L52; O31; O32; O38; 330; drug development phases; dynamics; innovation management; merger and acquisition; pharmaceutical drug development; R&D capabilities